Konseling Pranikah dalam Mengatasi Helicopter Parenting - Paais, Angel Sara (SIKIP: Jurnal Pendidikan Agama Kristen, 2023)
The family is the main base in parenting for children. One of the parenting styles for children is helicopter parenting. Helicopter parenting involves parents such as hovering around children, assuming that it can save children from danger and prevent them from failure. So, the purpose of this study is to provide understanding to prospective Christian parents through premarital counseling to provide an understanding of good parenting styles for children without applying helicopter parenting, which can cause children to experience psychological pressure. This writing uses qualitative research with a literature approach carried out by collecting sources related to this writing. Overall, the results of this study show that helicopter parenting can trigger disorders in children's mental health, reduce self-confidence and it interfere with the nature of development of children's growth and development, hence the need for premarital counseling to overcome these parenting problems.